Biogenic synthesis of cerium oxide nanoparticles using petals of Cassia glauca and evaluation of antimicrobial, enzyme inhibition, antioxidant, and nanozyme activities. (October 2022) - Butt, Ayesha; Ali, Joham Sarfraz; Sajjad, Anila; Naz, Sania; Zia, Muhammad
Abstract: Cerium oxide nanoparticles (CeO2 NPs) are used in different research areas due to their distinctive attributes. This study reports the green synthesis of CeO2 NPs using the aqueous extract of Cassia glauca flowers. The XRD analysis confirmed the pure face-centered cubic fluorite structure of the NPs with average size of 3.20 nm. FTIR analysis showed the attachment of functional groups on the surface of NPs. SEM images presented agglomeration of nanoparticles with spherical and irregular structures. The NPs showed moderate total antioxidant capacity (43.5 ± 1.15 μgAAE/mg), reducing potential (40.3 ± 0.85 μgAAE/mg), and DPPH based free radical scavenging potential (40.6 ± 1%). Nanoparticles presented moderate inhibition of alpha-amylase enzyme (18.7 ± 0.65%) but significant inhibition of urease (73.9 ± 1.2%) and lipase (75.9 ± 0.8%) was observed. The NPs exhibited effective peroxidase mimetic activity (1.0 ± 0.04 mM/min/mg) against hydrogen peroxide. Antibacterial results showed weak to mild activity against different bacterial strains. The report concludes that Cassia glauca flowers can synthesize CeO2 NPs and the existence of oxygen vacancies in CeO2 NPs facilitates the shifting between Ce 3+ and Ce 4+ by interaction with H2 O2, extrapolating the environmental and biological uses of cerium oxide nanoparticles. Graphical abstract: Image 1 Highlights: CeO2 NPs are synthesized using aqueous extract of Cassia glauca flowers. Pure face centered cubic NPs of 3.75 nm size has functional groups on the surface. NPs displayed significant antioxidant, enzyme inhibition, and antimicrobial properties. NPs also exhibited effective peroxidase mimetic activity against hydrogen peroxide.